Sertões à flora: as espécies vegetais no massacre de Belo Monte - França, Flávio (2019)
The flora plays a peculiar role in Os sertões by Euclides da Cunha (1982 [1902]), participating in the conflict. This dissertation aimed to analyze the role played by the species of plants mentioned, studying the representation of the Caatinga and the Sertão, evaluating the botanical precision of the work and comparing with other literary works. The flora was identified based on botanical dictionaries and manuals; the flora of the conflict region was listed based on the SPLINK site. The comparison was made based on the similarity index of Jaccard, using PAST. Euclidean flora is a small part of the region's richness, making the similarity to the actual flora very low (Jaccard index <12%). However, it has a high similarity with the analyzed floras (Jaccard Index> 24%), except for that cited in Francisco Mangabeira. There were 163 plant citations, making a total of 64 different species. The most cited species was the umbuzeiro (13 citations, 8%), followed by caroá (croá) (8, 5%), after bromelia and mandacaru (7, 4.3% each), juazeiro, ouricuri, quixabeira and palmatória (palmatória-do-inferno) (6, c .3% each), macambira, xique-xique and jurema (calumbi) (5, 3% each), baraúna, cunanã, gravatá (caravatá), marizeiro (4, c 2.5% each). The personification of the vegetation corroborates the conception of the "sertanejo" of the semi-arid together with the Caatinga species, whose knowledge allows a closer approximation to these populations that were excluded from the precarious modern prosperity.